Complexity of context and orientation of figure in the corridor illusion - Fineman, Mark B (Perceptual and Motor Skills, 1981)
Keywords: dept.psy

Facilitation of stereoscopic depth perception by a relative-size cue in ambiguous disparity stereograms. - Fineman, Mark B. (Journal of Experimental Psychology, 1971)
Proposed that the cue of relative size may facilitate depth perception in accordance with a crossed or uncrossed disparity in stereograms in which both tendencies are equally represented. A concurrent concept was that the latency associated with the perception of depth in random-dot stereograms may be due, in part, to a cue conflict between binocular disparity and relative size. 4 male and 2 female graduate students were given 8 presentations of 5 stereographic stimuli, in which disparity was ambiguous but relative size was systematically altered. Ss were tested for direction of depth preferences and response latency. Both the relative-size effects and an uncrossed disparity bias were evidenced in the data. The latter effect was attributed to binocular rivalry between dissimilar elements in the stereoscopic half-fields. It is concluded that depth cue relationships are more complex than had been suggested by simple dominance theories. (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1971 American Psychological Association.
Keywords: Conflict (Psychology); Cues; Depth Perception; Female; Form Perception; Human; Male; Reaction Time; Size Perception; Vision; article; association; conflict; dept.psy; depth perception; female; human; male; pattern recognition; perception; reaction time; steroscopic depth perception facilitation, relative-size cue in ambiguous disparity stereograms; vision

The Nature of Visual Illusion - Fineman, Mark B. (Dover Publications, 1996)
Keywords: Problems, exercises, etc; Visual perception; Visual perception; dept.psy; faculty_collection

The Inquisitive Eye - Fineman, Mark B. (Oxford University Press, 1981)
Keywords: Problems, exercises, etc; Visual perception; Visual perception; dept.psy; faculty_collection

The effect of a moving dot transversal on the Poggendorff illusion - Fineman, Mark B; Melingonis, Mark P (Attention Perception & Psychophysics, 1977)
In attempting to derive the minimal component of the Poggendorff figure which would still produce an illusion, responses to three types of transversal were measured. One was the customary solid line type; a second type presented the two segments sequentially, alternating between them; and the third consisted of a moving dot which traveled the transversal path. Each transversal was shown with and without verticals, for a total of six conditions. Ten subjects in each condition adjusted the luminous transversal until the segments appeared to be collinear. Figures with verticals present showed a greater magnitude of illusion than those without, and discrepancies for moving dot transversals were greater than those for comparable solid line figures. Since alternating transversals were not significantly larger than solid line figures, it was concluded that the magnitude of the moving dot effect could not be attributed to temporal sequence. An eyemovement hypothesis was suggested instead. © 1977 Psychonomic Society, Inc.
Keywords: dept.psy; normal human; theoretical study; visual illusion

A comparison of the Ponzo illusion with a textural analogue - Fineman, Mark B; Carlson, Jeffrey (Attention Perception & Psychophysics, 1973)
The inappropriate constancy scaling notion of geometric illusions was explored by employing a textural analogue of the Ponzo figure. Ten Ss estimated the length of a horizontal line by equating it with varying companion lines in the context of the Ponzo figure, a textural analogue, and a baseline control in which the lines appeared with no surrounding contours. The textural analogue had the added feature of imposing no contours at the ends of the horizontal lines. It was found that length estimates were significantly different between the horizontals of the Ponzo figure and control stimuli, but not between the texture figure and a context-free control. The results suggest that inappropriate constancy scaling plays a minor role at best in the perception of geometric illusions. © 1973 Psychonomic Society, Inc.
Keywords: dept.psy; normal human; theoretical study; visual illusion